Ukraine War and Food Crisis - Ameneh Marzban; Negar Fani; Reza Faraji; Abed Khanizade; Mohsen Dowlati (Gonabad University of Medical Sciences, 2023)
The Food and Agriculture Organization of the United Nations (FAO) has stated that the world may face a food crisis with rising prices and products at risk due to the war in Ukraine. Food prices have already increased due to climate change and the coronavirus epidemic. After the war, the cost of wheat has risen more [1]. About a third of the world's wheat is supplied by Russia and Ukraine, known as Europe's breadbasket. Wheat shortages may occur as farmers in Ukraine cannot grow their crops [2].